2003
DOI: 10.1186/1471-2458-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Greek orthodox christian church fasting on serum lipids and obesity

Abstract: Background: No study to date has focused on the impact of Greek Orthodox Christian fasting on serum lipoproteins and obesity yet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
97
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 60 publications
12
97
0
1
Order By: Relevance
“…In recent years, much interest has focused on this special practice that is retained and is characteristic of the Mediterranean diet of Crete and its suggested beneficial effect on dietary habits and health (8)(9)(10)(11) . According to the Greek Orthodox Church dietary recommendations, fasting occurs at three major periods during the year: Christmas (50 d); Easter Lent (40 d); and the Assumption (15 d), in addition to almost every Wednesday and Friday.…”
mentioning
confidence: 99%
“…In recent years, much interest has focused on this special practice that is retained and is characteristic of the Mediterranean diet of Crete and its suggested beneficial effect on dietary habits and health (8)(9)(10)(11) . According to the Greek Orthodox Church dietary recommendations, fasting occurs at three major periods during the year: Christmas (50 d); Easter Lent (40 d); and the Assumption (15 d), in addition to almost every Wednesday and Friday.…”
mentioning
confidence: 99%
“…Papadaki et al, and Sarri et al have all found a significant decrease in body weight in studies performed on fasting Greek Orthodox Christian. 13,14 For Ramadan, Hallak et al, also found a significant decrease in weight at the end of this holy month. 17 In present study weight tend to decrease since the 15 th day of fasting.…”
Section: Discussionmentioning
confidence: 76%
“…Certain authors have found a significant decrease in TC and LDL-C during Ramadan, Greek Orthodox fasting and Daniel fasting. 13,14,20,31,32 In scientific literature, results are conflicting for triglycerides and HDL-C. 13,14,17,20,33 LDL / HDL and TC / HDL ratio decreased significantly at the end of the study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations